Verifikasi Aktivitas Penjualan pada Pembelajaran KIK Melalui Implementasi Sistem Penilaian Autentik bagi Siswa Kelas XI Kuliner Ijen Suites - Siti Raudah; Nunung Nurjanah; Yetti Setyorini (Jurnal Pendidikan Indonesia, 2026)
This study was motivated by the low accuracy of sales activity verification in the Creativity, Innovation, and Entrepreneurship (KIK) learning process. Students’ sales activities had not been optimally monitored because reports were prepared only in written form without authentic evidence. This study aimed to: (1) determine the implementation of an authentic assessment system in verifying sales activities in KIK learning; and (2) determine the improvement in the accuracy of sales activity verification in KIK learning following the implementation of the authentic assessment system. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which was conducted in two stages, namely the pre-cycle and Cycle I. The research subjects consisted of 35 eleventh-grade students of the Culinary Ijen Suites program at SMKN 3 Malang. Data were collected through observation and documentation using observation sheets and portfolio assessment sheets. The authentic assessment system was implemented through portfolio-based assessment assisted by Google Forms as a medium for reporting sales activities. The results showed that the implementation of portfolio-based authentic assessment improved the accuracy of sales activity verification. In the pre-cycle, the average score for the accuracy of sales activity verification was 1.00 (25%), which was categorized as very low, whereas in Cycle I it increased to 3.26 (81.5%), which was categorized as good. Furthermore, the sales activity aspect increased from 1.00 (25%) to 2.51 (62.7%), the sales evidence aspect increased from 1.50 (37.5%) to 2.54 (63.5%), and the sales recording aspect increased from 1.70 (42.5%) to 2.97 (74.2%). The findings imply that the use of portfolio-based authentic assessment through Google Forms can assist teachers in verifying sales activities more objectively, systematically, and with better documentation.